Seasonal Incidence of Shoot and Fruit Borer (Leucinodes orbonalis Guenee) of Brinjal in Mid-Hills of Meghalaya - Tripura, Ajit; Lalruatsangi, K.; Chatterjee, M. L.; Patra, Sandip (Indian Journal of Hill Farming, 2018)
The field experiments were conducted at Entomology Research Field, ICAR Research Complex for North Eastern Hill Region, Umiam, Meghalaya during kharif- 2015 and spring-2016 to study the seasonal incidence of shoot and fruit borer of brinjal with reference to different dates of transplanting. The experiment was laid out in randomized block design (RBD) with three replications. Seedlings of brinjal (variety: chhaya) were raised in three different nursery beds for different date of transplanting during each year. Brinjal seedlings (30days old) were transplanted in the plot size of 5m x 3m. Weekly observations were taken from randomly selected 5 tagged plants/ plot for brinjal shoot and fruit borer infestation on shoot from each planting. For fruit infestation, total number of fruits and infested fruits were recorded/plot during each harvesting from each replication. During 2015, considering the whole experimental period from April to September, it was observed that peak infestation of shoot and fruit borer on shoot and fruit were in the 1st week of August (34.20%) and in the 3rd week of August (46.75%), respectively whereas in 2016, irrespective of planting, the peak infestation on shoot and fruit were observed in the 4th week of April (21.00%) and 4th week of May (17.55%), respectively. Relative humidity had positive influence on fruit infestation during both the years.